Penile Enhancement Using Biodegradable Scaffolds Covered with Platelet-rich Plasma-Fibrin Glue, Mesenchymal Stem Cells for Micropenis - Tavakkoli Tabassi , Kamyar; Tafazoli, Nooshin; Hamidi Alamdari, Daryoush; Soltani, Salman (Urology Journal, 2024)
Purpose: Evaluation of preliminary cosmetic and functional outcomes of biodegradable scaffolds covered with platelet-rich plasma in penile girth augmentation. Materials and Methods: Between June 2016 and June 2018, 36 males who had a mean age of 28.91 years (range 20 - 48 years) with micropenis underwent this procedure. A mixture of platelets-fibrin glue and mesenchymal cells obtained from dermal fat tissue were prepared. Then the mixture was seeded on the pretreated tube-shaped poly lactic-co-glycolic acid scaffold and underwent a whole day of incubation. Following penile degloving, scaffolds were surgically implanted within the interface region of dartos and Buck’s fascia. The 5-point Likert scoring scale was used to evaluate the patients’ satisfaction with surgery. Results: Patients followed up for 6-12 (8 ± 2.86) months. The penile length in an erected state before surgery was 6.5 - 12.5 cm (9.08 ± 1.6) which enhanced to 7 - 14 cm (10.59 ± 1.71) after surgery (P < .0001). The penile girth before and after surgery were 8.49 ± 1.53 and 10.91 ± 1.96 cm, respectively (P < .0001). An augment in penile length and girth of 1.5 and 2.6 cm were achieved, respectively. Patients appraised surgical intervention on a rating of one to five. The highest possible score (5) was assigned by 27 %, 33 % expressed a very good mark (4), and 19 % gave a good mark (3). Conclusion: Covering the scaffold with a mixture of Platelets-Fibrin glue and mesenchymal cells seems a safe and feasible method for penile reconstruction surgery. More studies should be done to determine the effect of platelets- fibrin glue and mesenchymal cells for treating micropenis.